Separating ‘us’ And ‘them’ In Front Pages’ Headlines Of Malay-language Newspapers During Malaysian 14th General Election - Noor Adzrah Ramle; Akmar Hayati Ahmad Ghazali; Moniza Waheed; Julia Wirza Mohd Zawawi (Human Resource Management Academic Research Societ, 2024)
Indexed by ERA